Perancangan Sistem Informasi Manajemen Aset Pada Fakultas Farmasi Universitas Andalas - Iswandy, Eka; Alhamidi, Alhamidi; Asmara, Rini; Budiman, Arif (Jurnal Sistem Informasi Dan Informatika, 2025)
Designing and developing a web-based asset management information system for the Faculty of Pharmacy at Andalas University. The increase in the number of physical assets and the absence of a centralized management system have caused various problems in the process of recording, tracking, and reporting assets. This study employs the System Development Life Cycle (SDLC) approach, which includes the stages of planning, analysis, design, implementation, testing, and system maintenance. The developed system consists of several main modules, such as asset data entry, room management, asset movement tracking, and asset reporting. The implementation results show that the system can improve data accuracy, facilitate the tracking of asset conditions and locations, and support real-time data-driven decision-making.